1985
DOI: 10.1111/j.1432-1033.1985.tb08929.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca 125 and Ca 19–9: two cancer‐associated sialylsaccharide antigens on a mucus glycoprotein from human milk

Abstract: The cancer-associated antigens Ca 125 and Ca 19-9 were demonstrated by radioimmunoassay to form structural units of a mucus glycoprotein in human milk taken from healthy women four days after parturition. The glycoprotein precipitated with the casein fraction at pH 4.6 and was completely absent in the whey as judged from Ca 19-9 assay. It could be effectively enriched by phenol-saline extraction from soluble milk proteins and further purified by gel filtration on Sephacryl S300 and Sephacryl S400.The active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…Because sialyl Lea antigen is normally present on mucins in the lung (53) as well as the pancreas (54), salivary glands (35,54), milk (55), seminal fluid (56), and gut (54), serum mucinassociated antigen could arise from several sources. The pancreas is not the exclusive source of mucin-associated antigens in serum because high serum mucin-associated antigen levels do not depend on pancreatic function.…”
Section: Patients' Age In Yearsmentioning
confidence: 99%
“…Because sialyl Lea antigen is normally present on mucins in the lung (53) as well as the pancreas (54), salivary glands (35,54), milk (55), seminal fluid (56), and gut (54), serum mucinassociated antigen could arise from several sources. The pancreas is not the exclusive source of mucin-associated antigens in serum because high serum mucin-associated antigen levels do not depend on pancreatic function.…”
Section: Patients' Age In Yearsmentioning
confidence: 99%
“…Although the epitopes of CA125 and CA130 have not yet been fully determined, the antigen defined by anti-CA125 and anti-CA130 antibodies has been shown to be a heat-labile large molecular weight glycoprotein (Matsuoka et al, 1987;Masuho et al, 1984;Davis et al, 1986). The co-expression of tumour-associated carbohydrate epitopes has been suggested I::: co so0 50 40 on large molecular weight mucin; CA125 and CAl9-9 have been found to be present on a mucin glycoprotein from human milk (Hanisch et al, 1985). Epitopes of CA19-9 and DU-PAN-2 may be co-expressed on the same mucin molecule in varying proportions (Lan et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Tumour-associated antigens recognised by different monoclonal antibodies are sometimes similar to each other and can be co-expressed on the same molecule (Hanisch et al, 1985;Lan et al, 1987;Yu et al, 1991). We examined the similarity and co-expression of seven tumour markers, carcinoembryonic antigen (CEA), CA130, CA125, SLX, CAl9-9, SPanl, and tumour-associated glycoprotein 72 , in the culture supernatant of 15 cancer cell lines and in the sera of 58 cancer patients.…”
mentioning
confidence: 99%
“…The biochemical determination of the CA125 antigen has produced conflicting data with evidence suggesting that it is a protein, a mucin, a carbohydrate, or a membrane-associated glycoprotein [40]. The first biochemical analysis of the CA125 antigen, which was purified from human milk, suggested that it was a sialylsaccharide antigen carried on a mucin glycoprotein [41]. Based on the gene structure, it is suggested that CA125 antigen is a transmembrane protein, comprising an extracellular domain, a transmembrane region, and an intracellular domain [42].…”
Section: Biochemical Analysis Of Ca125: No Consensus About Its Molecumentioning
confidence: 99%